Development of an electronic aerosol atomisation system for generating three-dimensional (3D) cells in microencapsulations and microtissues characterisation - Leong, Wai Yean (2016)
Cell encapsulation is a micro technology widely applied in cell and tissue engineering, tissue transplantation and regenerative medicine. Various techniques had been developed for microencapsulation of cells but these techniques presented threat to the cells due to the harsh or chemical treatment applied. In this research, a simple and economic electronic aerosol atomisation system was proposed for producing calcium alginate microcapsules. The system was developed with the incorporation of a conventional syringe pump, a customised air pump and motor controller circuits. The microcapsules and 3D microtissues were biophysically characterised. For the output of the system, the microcapsules size slightly increased with the extrusion rates and decreased significantly with the airflow rates. At an extrusion rate of 20 μl/min and airflow rate of 0.3 l/min, microcapsules with a diameter ranging from 220 - 270 μm were generated. The polymerisation time for the microcapsules was approximately 10 minutes after the immersion in calcium chloride solutions. The microcapsules showed high porous surface structure in field emission-scanning electron microscopy (FE-SEM) imaging. Keratinocytes (HaCaT) and Oral Squamous Cell Carcinoma (ORL-48) cells at cell densities of 3 × 107 and 9 × 107 cells/ml, respectively were applied for encapsulation and successfully grew into microtissues after 16 days of culture. The fourier transform infrared (FTIR) spectroscopy of the 3D cells showed stretching in phosphate bond of Deoxyribonucleic acid (DNA) and Ribonucleic acid (RNA) backbone, lipid and protein. The cells of HaCaT and ORL-48 microtissues were viable and they were characterised by different nucleus size. Replating experiment demonstrated that the cells in the microtissues could spread and proliferate in the culture dish. The electronic aerosol atomisation system developed in this work has successfully produced microcapsules with controllable size and applicable for growing microtissues. The microtissues produced are potentially a useful cell model for the study of cytochemicals.